A Polycation‐Modified Nanofillers Tailored Polymer Electrolytes Fiber for Versatile Biomechanical Energy Harvesting and Full‐Range Personal Healthcare Sensing. (28th October 2021) - Li, Zihua; Xu, Bingang; Han, Jing; Huang, Junxian; Fu, Hong
Abstract: The emergence of fibrous energy harvesters and self‐powered sensors gives birth to functional wearable electronics. However, low power outputs, poor sensing abilities, and limited material selections have greatly restricted their developments. Herein, novel polycation‐modified carbon dots (PCDs) tailored PCDs/polyvinyl alcohol nanocomposite polymer electrolytes (NPEs) are prepared and used as dominating triboelectric materials to construct a new NPEs‐based fiber triboelectric nanogenerator (NPE‐TENG) for the first time. The filling of PCDs endows NPEs with enhanced ionic conductivity. The developed NPE‐TENG can respond to different mechanical stimuli with excellent flexibility and deliver a high power density of 265.8 µW m −1 . Self‐powered wearable sensor and smart glove based on NPE‐TENG are further developed, which can achieve skin‐level tactile sensing and joint‐related activities monitoring in a rapid, real‐time, and noninvasive way. As a sustainable power source, the NPE‐TENG can drive small electronics and light up hundreds of light‐emitting diodes. This study not only renders new insights into the development of triboelectric materials for fiber‐based TENG but also provides a direction for potential applications of fibrous biomechanical energy harvesters and self‐powered sensors in wearable electronics, personal healthcare monitoring, and human–machine interactions. Abstract : A novel polycation‐modified nanofillers tailored polymer electrolytes fiber is developed for fabricating a core‐sheath triboelectric nanogenerator (NPE‐TENG). The developed NPE‐TENG exhibited improved ionic conductivities and a high power density (265.8 μW m ‐1 ). As self‐powered wearable sensors, NPE‐TENG can achieve skin‐level tactile sensing and joint‐related activities monitoring. As sustainable power sources, NPE‐TENG can effectively drive small electronics.